SSSR i Latinskaja Amerika. 1917-1967. [Pod red. vstupl. V.V. Vol'skogo. Pri učast. V.I. Ermolaeva, A.I. Sizonenko, A.D. Bekareviča i dr.] ("Meždunarodnye otnošenija", 1967)
AN SSSR. Institut Latinskoj Ameriki.